POLISH EMIGRATION IN FRANCE AT THE BEGINNING OF THE TWENTIETH CENTURY - ANNA PACHOWICZ (Истраживања, 2017)
The main aim of the article is an attempt to show the life of Polish emigration in France in the first half of the 20th century and, above all, the circumstances and organization of the trips, the number of people, their distribution within the territory of individual departments, working conditions and the problem of assimilation. In those times, Poles were coming to work in France from the territory of Germany (Westphalia) and from Poland. France was a destination Poles were very keen on and emigrated to on several occasions. On the one hand, France needed workers and, on the other hand, the difficult economic situation prompted Poles to leave their country and look for work outside their borders. The Polish-French convention on emigration and immigration, concluded on 3rd September 1919, played an important role in this matter. It set out the rules that gave grounds for many Poles to leave Poland in the following years. Polish immigration in the 1920s and 30s was of economic nature. Poles chose to work in various branches of heavy industry, primarily in mining, metallurgy, construction, textile and, least profitable, agriculture. They had to get used to the new conditions of life such as learning the language, the culture and mentality of Frenchmen, which was different from Polish. For the first groups of Poles arriving in France, French was a serious problem, yet with each passing year the problem started to fade away. Poles were ambitious and tried to educate their children and young people. Working in France, despite many difficulties, meant an improvement of material conditions for them compared to those in Poland. Compared with the French workers, their position was much worse, their status was significantly lower, they performed physical work, they generally received lower wages, and did not have full occupational rights.